A 7.5 ka chronology of stable carbon isotopes from tree rings with implications for their use in palaeo-cloud reconstruction - Helama, Samuli; Arppe, Laura; Timonen, Mauri; Mielikäinen, Kari; Oinonen, Kari (Global and Planetary Change)
2018